Provider Perspectives Regarding the Health Care Needs of a Key Population: HIV‐infected Prisoners After Incarceration. (September 2015) - Sidibe, Turquoise; Golin, Carol; Turner, Kea; Fray, Niasha; Fogel, Cathie; Flynn, Patrick; Gould, Michele; Knight, Kevin; Wohl, David
Abstract : N/A: During incarceration, many HIV‐infected prisoners receive care and are adherent to medication. However, following release, many have difficulty engaging in HIV care and remaining on antiretroviral therapy. Community‐based service providers for HIV‐infected releasees have a deep understanding of the health needs and challenges these individuals face on community re‐entry. We conducted in‐depth qualitative interviews with 38 health care and service professionals in two southern U.S. states regarding the barriers releasees faced in meeting their health needs, including HIV care and treatment post release. Individual, community, and organization‐level barriers to HIV care and treatment adherence post release were identified, and offered unique insight into the ways that these multilevel obstacles affect HIV‐infected former prisoners' abilities to engage in care and access necessary social services. Provider perspectives should be considered when designing interventions to support HIV care after release.